Lactobacillus plantarum RS-09 Induces M1-Type Macrophage Immunity Against Salmonella Typhimurium Challenge via the TLR2/NF-κB Signalling Pathway - Zhao, Chenpei; Chen, Huan; Liang, Hao; Zhao, Xiaoyu; Tang, Wenli; Wei, Maolian; Li, Youzhi; Zhang, Jianlong; Yu, Xin; Chen, Guozhong; Zhu, Hongwei; Jiang, Linlin; et al. (Frontiers in Pharmacology, 2022)
Lactobacillus plantarum can interact with macrophages against bacterial enteropathy due to its potential ability to modulate macrophage polarization. However, this mechanism is not completely understood. TLR2 can recognize microbial components and trigger macrophage cytokine responses to different gram-positive strains. The aim of this study was to investigate whether probiotic Lactobacillus plantarum RS-09 can induce macrophage polarization against Salmonella Typhimurium infection via TLR2 signalling. BALB/c mice were preadministered RS-09 continuously for 7 days and then infected with Salmonella Typhimurium ATCC14028. Mouse RAW264.7 mononuclear macrophages were stimulated with RS-09 and coincubated with ATCC14028 or PBS controls. The results of the in vivo study indicated that RS-09 could relieve S. Typhimurium-induced splenomegaly, body weight loss and death rate. RS-09 also limited the colonization and translocation of S. Typhimurium in the gastrointestinal tract and thereby protected against infection. We also observed that RS-09 upregulated the production of M1 macrophage characteristics (e.g., CD11c and IL-6) against S. Typhimurium. Furthermore, RS-09 induced the expression of TLR2 in macrophages. In an in vitro study, treatment of RAW264.7 cells with RS-09 either concurrently with or before S. Typhimurium challenge enhanced the secretion of Reactive oxygen species and Nitric oxide. This effect was related to TLR2 and NF-κB activation. Based on these findings, Lactobacillus plantarum RS-09 was shown to modulate M1 macrophage polarization and induce TLR2-linked NF-κB signalling activity in the innate immune response to S. Typhimurium infection.